(18)F-fluorodeoxyglucose positron emission computed tomography for monitoring tumor response in esophageal carcinoma treated with concurrent chemoradiotherapy - Zhang, Peiliang (Oncol Lett, 2018)
The aim of the present study was to explore the value of (18F−)fluorodeoxyglucose positron emission tomography ((18)F-FDG PET) in monitoring the early tumor response of esophageal squamous cell carcinoma (ESCC) treated with concurrent chemoradiotherapy (CRT). A total of 48 patients with pathologically proven ESCC were retrospectively analyzed. All patients underwent two serial (18)F-FDG PET scans at baseline (pre-CRT) and 40 Gy/4 weeks of starting radiation therapy (inter-CRT). All patients received intensity-modulated radiotherapy (with a total radiation dose of 59.6 Gy) concurrently with cisplatin-based chemotherapy. The maximum standardized uptake value (SUV(max)) and metabolic tumor volume (MTV) were measured using (18)F-FDG PET. The percentage changes (Δ) in SUV(max) and MTV between two serial scans were calculated and were revealed to be associated with the objective tumor response (oTR), according to the Response Evaluation Criteria in Solid Tumors 1.1. Among the 48 patients, 20.8% achieved a complete response, 68.8% exhibited a partial response and the oTR rate was 89.6%. On the pre-CRT PET scans, the mean SUV(max) and MTV were 14.1±5.8 and 58.2±25.4 cm(3), respectively. Following 40 Gy irradiation over 4 weeks, the mean SUV(max) and MTV significantly decreased to 4.3±3.5 and 19.0±12.1 cm(3), respectively (P<0.001). A significantly higher ΔSUV(max) and ΔMTV was observed in the responders compared with that in the non-responders [0.71±0.16 vs. 0.51±0.26 (P=0.015); and 0.64±0.13 vs. 0.42±0.09 (P=0.001), respectively]. Univariate analysis revealed that ΔSUV(max) and ΔMTV were significantly associated with oTR (P=0.010 and P=0.001, respectively). ΔMTV was used as a predictor and a cut-off value of 54% discriminated responders from non-responders with a sensitivity of 69.8% and a specificity of 100% (P=0.001). The area under the receiver operating characteristic curve was 0.837 (95% confidence interval, 0.702–0.928). The results of the present study indicated that interim (18)F-FDG PET scans may provide early prognostic value for determining oTR in patients with ESCC undergoing treatment with CRT.